Assessing the acceptability to general practitioners of the French College of General Medicine’s recommendations on considering patients’ social situations: a Delphi study - Gladys Ibanez; Théo Duguet; Hugo Figoni; Sohela Moussaoui; Kim Bonello; Bastien Richard; Mariela Skendi (BMJ Open)
Background Social determinants of health (SDH) impact the health status of individuals around the world. General practitioners (GPs) can take into account the social situation of patients in their care practice. To this end, the College of General Medicine (CGM) issued recommendations in 2022 to propose 100 methods of action.Objective To assess the acceptability to GPs of the recommendations set out by the CGM to improve the consideration of the social situation of patients in consultations.Design Quantitative, cross-sectional, descriptive study, using the Delphi method.Setting The data were collected through the administration of a questionnaire to GPs practising in France.Participants Participants were recruited by email from the academic network of Sorbonne University. The only criteria for inclusion were to be a GP from Sorbonne University and to complete the full questionnaire. 25 participants were included.Interventions Proposals were grouped into 24 themes. Participants had to rate the acceptability of these themes by rating their degree of relevance and degree of applicability on a Likert scale.Primary outcome The primary outcome was the acceptability by GPs of proposals to take into account the SDH. Acceptability was defined as relevance with a median greater than or equal to 7 and applicability with a median greater than or equal to 7, in the absence of disagreements.Results After 2 rounds, 12 themes were accepted: 5 addressed interventions at the individual level (eg, ‘understanding the context of patients’ lives and identifying social difficulties’), 4 addressed interventions at the organisational level (eg, ‘communication actions aimed at vulnerable patient populations’) and 3 addressed interventions at territorial level (municipality and national). Relevance was very good for all of them, with median responses ranging from 8 to 9 and with no disagreement. Applicability was more mixed, with 12 themes deemed applicable. Justifications were provided through participants’ comments. Proposals were made to improve the applicability.Conclusion This study explored how SDH could be taken into account through the perspective of GPs in the context of the CGM’s recommendations. While all proposals were deemed relevant, some were not applicable. The findings emphasise the need for adaptations in the organisation of the practice, of care pathways and more generally, in the organisation of the health system. Those actions require the commitment of professionals and political actors.